Determination of the causes of the denied Philhealth claims in Dr. Fernando B. Duran, Sr. Memorial Hospital, 2008-June 2013. - Orenza, Ma. Lourdes Rosita A.
Reimbursements from Philippine Health Insurance Corporation (Philhealth) are often used as additional source of income of most health providers including Dr. Fernando B. Duran, Sr. Memorial Hospital (DFBDSMH) for the procurement of medicines, equipment and hospital facility repair. Other hospitals even distribute it among the employees as part of their benefits. However, a large number of denied Philhealth claims were recorded in DFBDSMH for the past five (5) years which resulted to a decreasing income of the hospital year after year. Upon the progression of this study, the denied Philhealth claims were described according to its type of Philhealth enrollee, the patient's hospital stay, the rendered clinical services of the hospital and the Philhealth benefit package used. The reasons of denied Philhealth claims were reviewed according to year to identify the trend annually and were further categorized into the factors relating to the reasons. The amount of denied Philhealth claims were also obtained and totaled. Different recommendations were provided to address the various reasons of the increasing denied Philhealth claims in DFBDSMH.